2017
DOI: 10.1007/s11239-017-1487-z
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of direct oral anticoagulant dosing for venous thromboembolism treatment

Abstract: Adherence to FDA-approved dosing for the direct oral anticoagulants (DOACs) based on renal function, hepatic function, and concomitant medications in a real-world setting has not been evaluated. The purpose of this retrospective cohort analysis was to determine the prescribing accuracy of DOAC dosing for venous thromboembolism (VTE) treatment compared with enoxaparin. The secondary outcomes were to describe the incidence of in-hospital VTE recurrence and bleeding on DOAC therapy. The study included 168 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Benefits of dose intensification and monitoring drug levels or coagulation assays warrants further investigation, particularly given the use of DOACs in obese patients [21]. The frequency of dosing discordance is consistent with published data [22,23]. Variation from approved doses may confer altered risk of treatment failure or adverse events.…”
Section: Discussionsupporting
confidence: 70%
“…Benefits of dose intensification and monitoring drug levels or coagulation assays warrants further investigation, particularly given the use of DOACs in obese patients [21]. The frequency of dosing discordance is consistent with published data [22,23]. Variation from approved doses may confer altered risk of treatment failure or adverse events.…”
Section: Discussionsupporting
confidence: 70%
“…Consistently, a similar descriptive study on the Danish patient safety database reported that the adverse medication incidents occurred mainly in the prescribing phase, and in about 80% of incidents the errors occurred at the time of sector changes (at the admission, at the discharge or ward changes) [5]. Among different error subtypes occurring in the prescribing phase, the wrong dosage and drug omission have been repeatedly found as the most common subtype [3,6,7]. The affected patients are usually polymorbid patients in advanced ages having already high risk of bleeding [8].…”
mentioning
confidence: 60%
“…From this population, all patients admitted to our in-patient wards, from 21.08.2017-20.08.2018, who concomitantly received at least two ACs were included in the study. Subsequently, the following patients have been excluded: [1] patients who received the anticoagulants separately, no overlapping prescription [2] patients treated with the combination of heparin/ heparin analogs and vitamin-K antagonists (VKA) [3] patients receiving heparin/ heparin analogs based on a weekly schedule such as patients with hemodialysis [4] patients receiving low-dose alteplase (= < 4 mg) as a catheter locking solution [5] patients treated with the combination of VKA and direct oral anticoagulants (DOACs) during bridging from DOACs to VKA [6] patients who explicitly refused participation in research.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this has been reported to be as high as 10 to 20% in other studies. 13,28,29 We demonstrated that these patients could be identified quickly through our nurse-led pathway and that timely corrective action and education were easily instituted by telephone.…”
Section: Risk Factors For Bleeding or Recurrencementioning
confidence: 91%